Final hours in the Pacific the Allied surrenders of Wake Island, Bataan, Corregidor, Hong Kong, and Singapore - Young, Donald J. 1930- (McFarland, 2011)
"From December 7, 1941, until the Battle of Midway in June 1942, the war with Japan was a losing one. Of those days, none was more trying than the final hours for the men trapped on Wake Island, Bataan, Corregidor, Hong Kong and Singapore. This book, outlining the end, covers the crucial days that led to their surrender"--Provided by publisher.